1980
DOI: 10.1073/pnas.77.8.4993
|View full text |Cite
|
Sign up to set email alerts
|

A transformation-defective mutant of Abelson murine leukemia virus lacks protein kinase activity.

Abstract: A transformation-defective mutant of Abelson murine leukemia virus (A-MuLV), called A-MuLV-P92td, has been isolated. The mutant encodes a serologically identifiable A-MuLV protein of molecular weight 92,000 (P92) but it lacks the ability to transform either fibroblasts or bone marrow lymphoid cells. In contrast to the protein made by transforming strains of A-MuLV, the protein made by A-MuLV-P92td does not becme phosphorylated during in vitro incubation with [gamma-32P]ATP. If the protein is mixed with protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 31 publications
0
57
0
Order By: Relevance
“…Both are phosphorylated on serine in vivo, but neither protein displays evidence of tyrosine phosphorylation activity in vitro or in vivo (15,20). Because the tyrosine kinase activity of v-abl is mediated by c-abl-derived sequences (31,35), it seems likely that the major structural alteration of c-abl that generated v-abl was an event that unmasked intrinsic kinase activity of c-abl.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both are phosphorylated on serine in vivo, but neither protein displays evidence of tyrosine phosphorylation activity in vitro or in vivo (15,20). Because the tyrosine kinase activity of v-abl is mediated by c-abl-derived sequences (31,35), it seems likely that the major structural alteration of c-abl that generated v-abl was an event that unmasked intrinsic kinase activity of c-abl.…”
mentioning
confidence: 99%
“…The expression of v-abl kinase activity is correlated with transformation of lymphoid cells in vivo and in vitro (24). In addition, deletion mutagenesis of the A-MuLV genome (21), as well as structural analysis of naturally occurring mutants (35), has revealed that both the transforming activity and the tyrosine kinase activity are encoded in the 45-kilodalton region on the carboxyl side of the gag-abl junction. A subset of this region contains sequences highly homologous to tyrosine kinases encoded by other transforming genes (10,22).…”
mentioning
confidence: 99%
“…While the catalytic domain is fully contained in the c-abl protein and can be activated in properly designed in vitro assays (31), no in vivo occurrence of tyrosine kinase activity has yet been demonstrated for normal c-abl gene product (30,31,34). On the other hand, the acquisition of constitutive tyrosine kinase activity has been shown to be a requisite for the transforming activity of v-abl oncogene products (35,39,40,52,53). Ph' translocation of the c-abl gene in CML cells then offers a valuable opportunity for comparing, at the gene product level, a spontaneously activated human proto-oncogene with its retrovirus-transduced acutely transforming version.…”
Section: Discussionmentioning
confidence: 99%
“…The normal physiologic function of c-abl is presently unknown although its homologue v-abl is known to have tyrosine kinase activity (4). An abnormally large 8-kb ablrelated RNA transcript has been noted in CML cells (5,6) and this aberrant message appears to be transcribed from the translocated c-abl oncogene on the Ph'.…”
Section: Introductionmentioning
confidence: 99%